ҚАРАҚАЛПАҚСТАНДА МЕКТЕПКЕ ШЕКЕМГИ ТӘЛИМ СИСТЕМАСЫ ҲӘМ ОНЫҢ РАЎАЖЛАНЫЎЫ - Машарипова, А. (ILIM hám JÁMIYET, 2023)
This article includes much information from sphere of preschool education and based on sources about the enrollment of preschool children in preschool education institution and the actioties of organization.